Steffen K, Abdalati W and Stroeve J (1993) Climate sensitivity studies of the Greenland ice sheet using satellite AVHRR, SMMR SSM/I and in situ data. Meteorology and Atmospheric Physics 51(3–4): 239–258. DOI:10.1007/bf01030497. (August 2021) - Box, Jason E.; Stroeve, Julienne C.; Abdalati, Waleed
Physical geographer Konrad "Koni" Steffen, lost 8 August 2020 in a crevasse on the Greenland ice sheet, was a pioneer in satellite remote sensing and field observations of the Greenland ice sheet. This Classics Revisited piece honors the memory of Koni Steffen and examines the impact of a work which laid the foundation for numerous studies that made the Greenland ice sheet and the man global icons of climate change.